The Early Welsh Cult of Arthur: Some Points at Issue - Breeze, Andrew (Studia Celtica Posnaniensia, 2016)
A recent discussion of Arthur and Wales prompts a reply, using up-to-date research. It offers these surprising conclusions. Arthur really existed: he is not a myth or a legend, but historical. He will not have been Welsh, but a North Briton, and perhaps a Strathclyder. His battles, fought against other Britons and not the English, can all be located in southern Scotland and the Borders. Camlan, where Arthur fell, can be securely dated to 537 (after the Welsh annals) and situated north of Carlisle on Hadrian’s Wall (as proposed in 1935 by O. S. G. Crawford). The battle of Mount Badon in 493 will, however, have nothing to do with Arthur or North Britain. It was a British victory over the English, fought near Swindon and perhaps at the hillfort of Ringsbury overlooking Braydon Forest. Proponents of a Northern Arthur, like Rachel Bromwich (1915-2010) and Charles Thomas (1928-2016) can thus be vindicated against those rejecting a Northern Arthur, like Professor Kenneth Jackson (1909-91) of Edinburgh.